2021
DOI: 10.14693/jdi.v28i2.1234
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Shaping Ability between Continuous Rotary and Manual Instrumentations in Pediatric Endodontics

Abstract: Objective: The aim of this in vitro study was to evaluate the efficacy of rotary EndoArt Ni-Ti Gold Pedo Kit and K-files in shaping ability, canal transportation, centering ability and instrumentation time in primary molars. Methods: For the study total of 30 extracted primary molars root with minimum 7mm root length were selected. Shaping of root canals in primary molars were done using the two systems, and CBCT and specialized software were used for scanning and analysis of pre-operative and post-operative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…The lower tendency toward apical transportation in the rotary file systems may be credited to its design with a non-cutting tip [ 5 , 10 ]. This agreed with Güçyetmez et al [ 32 ] study in which a non-significant statistical difference in the apical transportation values was found between K-files & EndoArt rotary files. The highest mesial transportation in the Kedo-S Square group was found in the middle third (40%) in this study while the highest mesial transportation in the Fanta AF™ Baby group was present in the apical third (56%); this may be clarified by the operator’s tendency to do more vigorous preparation on the side opposite to the most favorable support.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lower tendency toward apical transportation in the rotary file systems may be credited to its design with a non-cutting tip [ 5 , 10 ]. This agreed with Güçyetmez et al [ 32 ] study in which a non-significant statistical difference in the apical transportation values was found between K-files & EndoArt rotary files. The highest mesial transportation in the Kedo-S Square group was found in the middle third (40%) in this study while the highest mesial transportation in the Fanta AF™ Baby group was present in the apical third (56%); this may be clarified by the operator’s tendency to do more vigorous preparation on the side opposite to the most favorable support.…”
Section: Discussionsupporting
confidence: 92%
“…The present study findings agreed with Mohamed et al [ 5 ] who revealed that the Kedo-S Square file had a minimal quantity of removed dentin contrasted to manual K- & H-files. However, it was disagreed with Güçyetmez et al [ 32 ] who concluded that EndoArt rotary files eliminated more dentin than K-files in the coronal and middle root canal thirds. Using pairwise comparison, a statistically significant difference was found between Kedo-S Square and K-files at different root canal levels in the amount of the removed dentin on both mesial and distal sides.…”
Section: Discussionmentioning
confidence: 92%
“…Literatür tarandığında EndoArt eğesiyle ilgili yapılmıĢ sadece iki çalıĢma mevcuttur. Bu çalıĢmaların birinde eğenin döngüsel yorulma direnci incelenmiĢ (31) diğerinde ise süt diĢlerinde EndoArt Pedo Kitmanuel K-tipi el eğesi preparasyon yeterliliği açısından karĢılaĢtırılmıĢtır (32). Piyasaya yeni sürülen bir döner eğe sistemi olduğu için eğenin kanal yenileme sırasında apikalden taĢan madde miktarı ilk kez çalıĢmamızda incelenmiĢtir.…”
Section: Gi̇ri̇ş 20unclassified